Structural analysis of composite components considering manufacturing effect. (15th April 2016) - Mayer, Natalie; Prowe, Jens; Havar, Tamas; Hinterhölzl, Roland; Drechsler, Klaus
Abstract: An improvement of a structural simulation for composite structures is realized with data sets from process simulations. A main challenge is to provide a mesh-independent interface for finite element (FE) data conversion. In this work, the FE data conversion for structural analysis is discussed. All relevant material parameter and model data can be exchanged with a mesh-independent method, between different process simulation tools and tools for a subsequent mechanical analysis. This approach is based on mapping algorithms and a common data format definition. An approximated FE field value is transferred into the target mesh with respect to the corresponding coordinate system and the material structure. In this paper, different models for subsequent material prediction of sheared woven fabric composites are considered and validation results for several analytical meso-modeling strategies of stiffness properties for such fabrics are demonstrated.